2020
DOI: 10.1111/eth.13003
|View full text |Cite
|
Sign up to set email alerts
|

Blinking behavior in great‐tailed grackles (Quiscalus mexicanus) increases during simulated rainfall

Abstract: Animals often adjust their behavior in response to changes in environmental conditions, and these behavioral adjustments may result from sensory constraints. In particular, rainfall influences behavior but our understanding of its effects on visual abilities is limited. This study, therefore, tested the hypothesis that rainfall influences blinking behavior, a major component of visual processing, in captive great‐tailed grackles (Quiscalus mexicanus). The blinking behavior of the grackles was recorded when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Although we conducted our sampling in the field, this could be done using video footage. Being able to analyze video footage means that information about blink duration can also be collected, and previous studies have demonstrated that this additional metric can also vary between individuals and species (Beauchamp, 2017; Matsumoto‐Oda et al, 2018; Rands, 2021; Tada et al, 2013; Yorzinski, 2020a; Yorzinski & Argubright, 2019), and may increase in relation to group size (Beauchamp, 2017). From a field observation perspective, being able to zoom in on detail may also be extremely useful if the observed individuals are a long distance away (as we acknowledge we were lucky with being able to get within 100 m of our sample animals).…”
Section: Discussionmentioning
confidence: 99%
“…Although we conducted our sampling in the field, this could be done using video footage. Being able to analyze video footage means that information about blink duration can also be collected, and previous studies have demonstrated that this additional metric can also vary between individuals and species (Beauchamp, 2017; Matsumoto‐Oda et al, 2018; Rands, 2021; Tada et al, 2013; Yorzinski, 2020a; Yorzinski & Argubright, 2019), and may increase in relation to group size (Beauchamp, 2017). From a field observation perspective, being able to zoom in on detail may also be extremely useful if the observed individuals are a long distance away (as we acknowledge we were lucky with being able to get within 100 m of our sample animals).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about how blinking differs between species, and more detailed comparative studies comparing the behaviour both between and within species are needed, with larger sample sizes taken within species (as the current data were based on observations of between one and five individuals in captive conditions, which could conceivably mean that some of the results used were atypical for a species). This would need to be done using a suitably standardised technique ( Tada et al, 2013 ) to allow comparison between species, as blinking behaviour is likely to be affected by environmental conditions ( Nakamori et al, 1997 ; Yorzinski & Argubright, 2019 ; Yorzinski, 2020a ). The reanalysis presented here highlights that care needs to be taken when considering data from related species, and that phylogenetically-controlled correlations may exist with ecological data from existing datasets.…”
Section: Discussionmentioning
confidence: 99%
“…This would need to be done using a suitably standardised technique (e.g. (Tada et al, 2013)) to allow comparison between species, as blinking behaviour is likely to be affected by environmental conditions (Nakamori et al, 1997;Yorzinski and Argubright, 2019;Yorzinski, 2020a).…”
Section: Discussionmentioning
confidence: 99%